Hubungan antara konsep diri dan efikasi diri terhadap kesiapan kerja siswa SMK Negeri 5 Kerinci (Indonesian Journal of Counseling and Development, 2022)
This study aims to determine the relationship between self-concept and self-efficacy in job readiness in class XII students at SMK Negeri 5 Kerinci. This research is a type of quantitative research with a correlational approach. The number of samples in this study was 59 students from class XII. The instruments used to collect data in this study were the scale of work readiness, self-efficacy, and self-concept. The data was processed using the Multiple Regression analysis methods with the help of a computer through the SPSS Version 21 application. The results showed that the correlation coefficient between self-concept and work readiness was 0.804 with a significant value of 0.000